ETHNOPHARMACOLOGICAL STUDY OF PLANTS, IN SUBURBAN POPULATIONS OF THE MUNICIPALITY OF CAMPECHE (MEXICO), FOR THE TREATMENT OF PARASITOSIS - Mex-Álvarez Rafael Manuel de Jesús1*,Guillen-Morales María Magali2, Garma-Quen Patricia Margarita3, Yanez-Nava David4, Chan-Martínez Roger Enrique5, May-Suárez Oscar Adrián6 , (Chelonian Research Foundation, 2024)
Medicinal plants are an important resource for the health of rural residents because they live in areas where infectious diseases, particularly parasitic infections, are very frequent and the lack of health services prevents effective treatment. The objective of this study was to provide an updated critical analysis of the ethnopharmacology of medicinal plants used in the treatment of parasitic diseases in the State of Campeche, Mexico. The ethnopharmacological knowledge of five communities was studied through 247 interviews with prior consent from the informants. The survey was based on a semi-structured questionnaire with simple and flexible language to collect additional information that the residents provided. It was found that in the localities studied there is still social knowledge of the use of plants in the treatment of human parasitosis but this knowledge is at risk because there is no formal dissemination and the transgenerational transmission of knowledge is being lost. Keywords: Public Health, Herbal Medicine, Medicinal Plants.